Room 13 - Swindells, Robert 1939-; Riley, Jon (New York : Oxford, 2009)
New educational edition of Robert Swindells' spooky classroom classic Improve your English, and reading, skills with unabridged contemporary literature. Somebody was in there. Somebody - or some thing ... There is no Room 13 in the creepy Crow's Nest Hotel, where Fliss and her friends are staying on a school trip. Or is there? For at the stroke of midnight, something peculiar happens to the door of the linen cupboard next to Room 12. And something is happening to Ellie-May Sunderland, too - something very sinister
Keywords: Novela juvenil inglesa -- Siglo XX; Historias de terror